New urban decentralization: space and sensoriality. The “sensory heritage” as a perceptual and community-based approach for reading the postmetropolitan landscape - Castaldo, Giovanni; Mocchi, Martino (Urban, 2016)
The twentieth century, that Hobsbawm defined as “the short century” (Hobsbawn, 1995), was characterized by a high incidence of political, economic and social events, that determined the progressive identification of society with the immediate present, to the detriment of the past and memory mechanisms. This led to the establishment of a sort of “permanent present”, which influenced the way of considering and organizing the places of social life: the cities. One of the elements having had the highest impact on the twentieth century approach to the city has to be found in the close relationship that developed between space management and ideology. For Western society, this is, indeed, a well-known issue from its very origins: the relationship between “the system of beliefs and opinions that represent a particular social group”, namely ideology, and the consequent shape of the space, is a fact that has accompanied the birth of the city itself. It is precisely in the light of this gap that the Greek pòlis was born, namely in the very moment when «rationality identifies itself with politics» (Vegetti, 1977: 25). More specifically, the management of public affairs and space (politics), becomes expression of an ideology (lògos). The evolution of the city during the last century led to a condition of growing complexity, where finding new proper tools for interpreting and managing urban transformations is getting increasingly hard. Therefore the issue of urban decentralization, as a possible solution to face the alienation of contemporary metropolitan areas through processes of participation and social cohesion, is nowadays again particularly relevant both in Italy and internationally. Italy has recently launched a major reform (Law n. 56/2014) in the field of metropolitan areas regulation, calling for public attention to the issue. The approach presented in this paper, based on the concept of multisensoriality as a key element for the urban landscape reading, represents a complementary methodology running parallel to the traditional tools.